Healthy Singleton Pregnancies From Restorative Reproductive Medicine (RRM) After Failed IVF - Boyle, Phil C.; de Groot, Theun; Andralojc, Karolina M.; Parnell, Tracey A. (Frontiers in Medicine, 2018)
Objectives: To determine the live birth rate for patients who chose to undergo treatment with Restorative Reproductive Medicine (RRM) after previous IVF (includes ICSI). To look at birth outcomes with RRM after IVF, particularly rates of twin and higher order pregnancies, premature birth, low birth weight, and potential cost savings achieved with RRM. Setting: Two outpatient clinics in Ireland providing advanced RRM treatment of infertility. Materials and methods: All patients presenting between January 2004 and January 2010, with a history of infertility and previous IVF treatment were included if they proceeded beyond the initial consultation and began treatment. Main outcome is live birth per couple calculated using life table analysis. Results: 403 patients met the study criteria, among which 74 had a subsequent live birth. These women had significant negative predictive characteristics for healthy live birth including: advanced reproductive age (average 37.2 years), an average of 5.8 years of infertility with 2.1 (range 1–9) previous IVF attempts, with only 5% having previously had a live birth from IVF. Despite these undesirable prognostic indicators, the overall RRM live birth rate was 32.1% (crude 18.4%). Women aged 35–38 had a live birth rate of 37.5% (crude 23.6%) and older women over 40 had a live birth rate of 27.4% (crude 16.0%). The average birth weight was 3374g (7lb 7oz) with 92% being born at 37+ weeks and no very low birth weight babies. There was only one twin pregnancy in the study population; the potential health care savings for avoidable multiple pregnancies in these patients was estimated at £205 672 (USD$284 915). Conclusions: Patients who have already tried IVF can achieve comparable live birth outcomes with RRM compared to another cycle of IVF. RRM has a low risk of twin or multiple births, and very good neonatal outcomes with a potential cost savings to the health care system.